2022
DOI: 10.3390/ijerph19159413
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Study Investment: An Analysis of the Defense Mechanisms Characterizing Studyholism and Study Engagement

Abstract: Defense mechanisms are unconscious processes that protect a person from excessive anxiety. They are part of everyday functioning, and mature defenses are associated with positive outcomes. However, the excessive use of defenses or the use of immature defenses is associated with psychopathology. The present study aims to analyze the defense mechanisms that characterize two types of heavy study investment: Studyholism and Study Engagement. We performed a path analysis, MANOVAs, and binary logistic regressions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…At the same time, hypothesis H2 was confirmed. In line with previous studies (Loscalzo & Giannini, 2021, 2022a, 2022a, 2022b), our result supports the conceptualization of Studyholism as an OCD-related disorder, due to the over-thinking tendency that seems to characterize studyholics and that in this study is confirmed by the association between Studyholism and insomnia. More specifically, we suggest that college students with high levels of Studyholism might ruminate about their academic situation, and in turn, develop sleep problems (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At the same time, hypothesis H2 was confirmed. In line with previous studies (Loscalzo & Giannini, 2021, 2022a, 2022a, 2022b), our result supports the conceptualization of Studyholism as an OCD-related disorder, due to the over-thinking tendency that seems to characterize studyholics and that in this study is confirmed by the association between Studyholism and insomnia. More specifically, we suggest that college students with high levels of Studyholism might ruminate about their academic situation, and in turn, develop sleep problems (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we speculate that Studyholism might be associated with other adverse physical and psychological outcomes. More specifically, besides sleep quality impairment and daytime sleepiness, it might predict insomnia, also in light of the obsessive (and over-thinking) nature of Studyholism (Loscalzo & Giannini, 2021, 2022a, 2022a, 2022b) that might cause difficulties in falling asleep. Moreover, we might also expect an association between Studyholism and emotional exhaustion, a burnout feature.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive diligence in the educational process can be a sign of social maladaptation. This conclusion is reached by the authors of the article Y. Loscalzo, M. Giannini, investigating the psychological mechanisms of protection of students and their involvement in learning [3]. In their opinion, social anxiety and anxiety can be compensated by students due to high involvement in studies.…”
Section: Introductionmentioning
confidence: 97%
“…In another paper, the same authors noted that "psychologically stable and adaptive students report the highest GPA" (Vlachopanou & Karagiannopoulou, 2022). If the highest GPA, however, is related to heavy study engagement, this standpoint provided limited support to a study by Loscalzo & Giannini (2022) that found an increased probability for social impairment and clinically relevant symptoms to be hidden by hard studying. When analyzing defense mechanisms characterizing studyholism and study engagement, they suggested that studyholism was positively predicted by regression which is maladaptive defense and hence, studyholism might be regarded as a potential clinical condition.…”
Section: Discussionmentioning
confidence: 99%